Art sense : sensing the arts in the everyday - Devilles, Gary C.; Malquez, Reagan ; Tolentino, Rolando B. (Quezon City, Philippines, 2008)
Using interdisciplinary studies that cover the past twenty years, specifically feminism, postcolonial studies, human geography, and the most recent, affect theory and sensory studies, engagement with art objects becomes an exercise in self-reflexivity. From seeing, touching, or hearing an artwork, we get a sense of paradox, potentiality,or possibility. This textbook, aptly titled Art Sense: Sensing the Arts in the Everyday, creates an opportunity for critical engagement and reflexivity as students explore, examine, and evaluate the arts and their aesthetic experiences in the everyday life. - - Excerpt from the Back Cover
Keywords: Art appreciation -- Study and teaching; Arts -- Study and teaching -- Philippines